Rancang Bangun Sistem Informasi Koperasi Simpan Pinjam Pembiayaan Syariah Berbasis Kelompok - Fayruz Rahma (Jurnal Nasional Teknologi dan Sistem Informasi, 2018)
A group-based sharia savings and loan cooperative is different with the common cooperatives out there. This unique cooperative’s process business made its staff not being able to use a usual cooperative information system without being customized. A SWOT analysis has been conducted to decide whether this kind of cooperative need to develop a new information system or not. The results showed that a new information system is definitely needed. An information system of sharia-based savings and loan cooperative with special features to handle group transactions of cooperative members has been designed and developed, although it’s not yet perfect, to help ease the staffs’ workloads. User centered design approach was used to develop this information system since the users are the ones who know best what they need and do. Several diagrams were created to design the system, such as: use case diagram, architecture system diagram, data flow diagram, entity relationship diagram, and the user interface mockup. This information system has several main modules, such as: Member Service, Transaction, Authorization, Back-Office, Reports, and System Configuration. Blackbox tests have been done to test whether the system is functioning properly or not.